Convergence of Colonial Politics, Islamic Ideology, and Popular Resistance: An Analysis of the Background of the Aceh War (1873-1903) - Airlangga, Zetira Novian; Akbar, Ichsan Kurnia; Lingga, Wahyu Rafael; Maler, Wani; Narny, Yenny (Analisis Sejarah, 2025)
The Aceh War (1873-1903) was one of the most critical and protracted armed conflicts in the history of Dutch colonialism in the Indonesian archipelago. This article aims to examine the background of the Aceh War through a thematic approach to three key aspects: colonial political expansion, the influence of Islamic ideology, and community participation, as manifested in the "People's War" (Perang Semesta). The study employs a descriptive qualitative approach grounded in a review of secondary sources, including historical books, academic papers, and digital archives. The findings show that the conflict was fueled not just by Dutch colonial ambition following the 1871 Sumatra Treaty, but also by jihad discourse bolstered through religious writing like The Hikayat Perang Sabil and collective social opposition. This research highlights the importance of an interdisciplinary approach in understanding local resistance as a multifaceted manifestation of political, cultural, and spiritual conflict.